Assessing the Enabling Governance Environment to Promote and Enforce Women's Rights in the Southern Caucasus - World Bank (Washington, DC, 2017)
After the collapse of the Soviet Union, Armenia, Azerbaijan, and Georgia experienced a sharp decline in economic output, prolonged regional conflicts resulting in great numbers of internally displaced persons (IDPs) and refugees, the deterioration of social protection systems, and devastating natural disasters. These circumstances resulted in a dramatic increase in poverty and a decline in the human development index. Poverty has greatly affected women and introduced numerous obstacles and challenges in the promotion of gender equality and advancement of women's rights. Furthermore, women face new challenges with regard to issues such as human trafficking, rights of IDPs, and peacekeeping initiatives. Regional cooperation is necessary to address these issues. This project set out to assess the capacity of civil society organizations (CSOs) to meet the pressing needs for legal literacy, legal aid, and improved access to justice and legal services for poor women in Armenia, Azerbaijan, and Georgia. The primary objectives were as follows: identify laws and institutions that promote women's rights; identify and disseminate successful initiatives that promote women's legal rights and legal literacy and facilitate their access to legal services; and strengthen collaboration among groups working on gender issues in prioritizing women's legal rights. This report is organized around three key dimensions of gender equality: the status of women as far as human capital development is concerned, their status in terms of access to productive resources, and their status and protection under the law.